The Correlation Between Implementation of the Merdeka Curriculum and Students’ Learning Independence in Science Learning Among Eighth-Grade Students at SMP Negeri 48 Samarinda: Hubungan Implementasi Kurikulum Merdeka dengan Kemandirian Belajar Siswa dalam Pembelajaran IPA - Riskhy, Friska; Herliani; Maasawet, Elsje T.; Makkadafi, Suparno P. (UNIB Press, 2025)
This study aimed to determine the relationship between the implementation of the Merdeka Curriculum and students’ learning independence in Science subjects among eighth-grade students at SMP Negeri 48 Samarinda. This research employed a quantitative approach with a correlational method. The sample consisted of 100 students selected using stratified random sampling from a total population of 128 students. Data was collected using a closed-ended questionnaire based on a Likert scale. The data analysis techniques included normality testing, linearity testing, and Pearson Product Moment correlation. The results showed that the implementation of the Merdeka Curriculum was categorized as